2021
DOI: 10.1002/jctb.6791
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow reactors for cultivating aerobic granular sludge: configuration innovation, principle and research prospect

Abstract: Efficient start‐up, cultivation and maintenance of aerobic granular sludge (AGS) in continuous flow reactors (CFRs) is critical for its full‐scale application in wastewater treatment plants (WWTPs). The successful implementation of AGS under continuous flow condition depends on the configuration of CFR that provides the selective pressures and hydraulic shear force (HSF) to sludge required for rapid granulation. Important progress has been witnessed with respect to CFR configurations in recent decades for in‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…Kent et al [14], e.g., emphasized that the stable cultivation of compacted granules is critical for operating an AGS-CFR unit; although it was also highlighted that the granulation process is still unstable under long-term operation in both SBR and CFR regimes [14]. Yan et al [12] pointed out that the risk of instability is higher in CFR mode. Current literature reports several factors that influence the granulation process in AGS system, known as ''selective pressures''.…”
Section: Operation Modes Of Granular Sludge Unitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kent et al [14], e.g., emphasized that the stable cultivation of compacted granules is critical for operating an AGS-CFR unit; although it was also highlighted that the granulation process is still unstable under long-term operation in both SBR and CFR regimes [14]. Yan et al [12] pointed out that the risk of instability is higher in CFR mode. Current literature reports several factors that influence the granulation process in AGS system, known as ''selective pressures''.…”
Section: Operation Modes Of Granular Sludge Unitsmentioning
confidence: 99%
“…The authors clarified that the longer SRT, the lower biomass yield rate. Yan et al [12] reported that the AGS systems work usually with a SRT two times longer than that in the CAS. This clarification meets the perspective of Bengtsson et al [8].…”
Section: Aerobic Granular Sludge Generationmentioning
confidence: 99%
See 3 more Smart Citations